A Strategy for Wafer‐Scale Crystalline MoS2 Thin Films with Controlled Morphology Using Pulsed Metal–Organic Chemical Vapor Deposition at Low Temperature. Issue 4 (17th December 2021) - Choi, Jeong‐Hun; Ha, Min‐Ji; Park, Jae Chan; Park, Tae Joo; Kim, Woo‐Hee; Lee, Myoung‐Jae; Ahn, Ji‐Hoon
Abstract: 2D semiconductor materials with layered crystal structures have attracted great interest as promising candidates for electronic, optoelectronic, and sensor applications due to their unique and superior characteristics. However, a large‐area synthesis process for various applications and practical mass production is still lacking. In particular, there is a limitation in that a high process temperature and a very long process time are required to deposit a crystallized 2D material on a large area. Herein, pulsed metal–organic chemical vapor deposition (p‐MOCVD) is proposed for the growth of wafer‐scale crystalline MoS2 thin films to overcome the existing limitations. In the p‐MOCVD process, precursors are repeatedly injected at regular intervals to enhance the migration of precursors on the surface. As a result, crystalline MoS2 is successfully synthesized at the lowest temperature (350 °C) reported so far in a very short process time of 550 s. In addition, it is found that the horizontal and vertical growth modes of MoS2 can be effectively controlled by adjusting key process parameters. Finally, various applications are presented by demonstrating the photodetector (detectivity = 18.1 × 10 6 at light power of 1 mW) and chemical sensor (response = 38% at 100 ppm of NO2 gas) devices. Abstract : Crystalline MoS2 layers are successfully formed at wafer‐scale sizes by a pulsed metal–organic chemical vapor deposition process at a low temperature of 350 °C. MoS2 growth mode is controlled by adjusting the growth pressure and Ar/H2 S flow rate ratio. The photodetection and gas sensing characteristics are investigated using MoS2 layers with different morphologies, and potential uses in various devices are suggested.